Narcissistic Attitudes of Disney Villainesses in Serena Valentino’s Series - Grace Hotmauli Gultom (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study analyzes narcissistic attitudes in five female villain characters in the Disney Villainesses series by Serena Valentino: Evil Queen, Lady Tremaine, Mother Gothel, Cruella, and Ursula. In the Serena Valentino series, initially these five female characters are depicted as good characters, but slowly they become evil characters. With that, this study aims to explore how their narcissistic attitudes such as manipulative, a need for validation and lack of empathy to others slowly develop within them. Otto Kernberg's narcissism theory is used to see how early trauma, feelings of insecurity, and disappointment shape the narcissistic attitudes of the characters, making them manipulative, needing validation, and lacking empathy for others. The results of the analysis show that painful past experiences greatly influence the development of narcissistic attitudes that shape the way they manipulate others, demand validation, and lack empathy for others.